DETERMINANTS OF LOW BIRTH WEIGHT IN FULL TERM PRIMIGRAVIDS. - Ambreen Shahriyar 1 , Maryam Faiz Qureshi 2 , Farida Wagan 3 , Razia Tariq 4 , Naseem Mallah 5 , Rashda Ghumro 6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT BACKGROUND: The low birthweight (LBW) is counted as the most crucial predictor of infant mortality, especially the deaths during initial days of life. This urges the depth knowledge of risk factors for LBW as significant for identification, recognition, awareness and providing appropriate care to all mothers. OBJECTIVE: To determine the frequency and risk factors of LBW fetus in full term primigravids at Peoples Medical University & Hospital (PUMHS) Nawabshah. DESIGN: Descriptive cross-sectional study. PLACE OF STUDY: This study was conducted at Obstetrics and Gynecology Department of PUMHS Nawabshah. DURATION OF STUDY: The duration of this study was six months. METHODOLOGY: After ethical approval, the study consisting of 243 patients was conducted. Detail history taken regarding, Socioeconomic-Status, Profession, History of (smoking, hypertension, alcohol-intake, pica- (Multani-mitti), anemia, diabetes-mellitus (DM) and oligohydramnios followed by special investigation for hemoglobin (Hb) and ultrasound-pelvis were done. Primigravids of all age group with full-term pregnancies irrespective of delivery mode (Normal/Operative) were included. Antenatal mothers with diagnosed cardiac disorders were excluded. RESULTS: The mean age was 25.56±4.73 years. Predominantly patients presented with history of hypertension in 38(15.6%) and Pica-(Multani-mitti) 36(14.8%). Gestational DM in 20(8.2%) and Smoking in 6(2.5%) of cases was recorded. The Hb ranging from a minimum of 3.50 grams per deciliter to 14.0 grams per deciliter and LBW<2500 gm in 54(22.2%) cases. CONCLUSION: LBW a common problem in Pakistan. Among different risk-factors BMI, Socioeconomic-Status, mother’s-profession, smoking, hypertension, alcohol-intake, pica-(Multani-mitti) and gestational DM were found to be the important risk-factors contributing to LBW babies born